INTERCORRELATION OF INSOMNIA, SLEEP DURATION, INTERNET USE DURATION AND INTERNET ADDICTION ON MILLENNIAL IN JAKARTA - Hendro Prabowo; Mahargyantari Purwani Dewi; Nadia (Dinasti International Journal of Education Management And Social Science, 2020)
With 171,260,000 internet users, Indonesia is the fifth of the internet users in the world. This study aims to examine the intercorrelation between insomnia, sleep duration, internet use duration and internet addiction in 259 millennial respondents. The instruments used were the Insomnia Severity Index (ISI) and the Internet Addiction Test (IAT). The results showed that 79.5% of the participants had sleep duration of less than 6.5 hours per day and 72% of them were also reported had internet use duration of more than 6 hours per day. Result also found that there is a positive correlation between insomnia and internet addiction, negative correlation between insomnia and sleep duration, positive correlation between insomnia and internet use duration, negative correlation between internet addiction and sleep duration, positive correlation between internet addiction and internet use duration, and negative correlation between sleep duration and internet use duration.